mTOR signaling contributes to motor skill learning in mice - Bergeron, Yan; Chagniel, Laure; Bureau, Geneviève; Massicotte, Guy; Cyr, Michel (Frontiers in Molecular Neuroscience, 2014)
The mammalian target of rapamycin (mTOR) kinase is a critical regulator of mRNA translation and is suspected to be involved in various long lasting forms of synaptic and behavioural plasticity. However, its role in motor learning and control has never been examined. This study investigated, in mice, the implication of mTOR in the learning processes associated with the accelerating rotarod task. We first observed that the rotarod learning did not alter the levels of total mTOR in the striatum, hippocampus, cerebellum and anterior cortex of trained mice. However, it increased the levels of phosphorylated mTOR in the striatum and hippocampus exclusively during the first session of training; no change was observed at the second and third sessions. In order to further investigate the potential role of mTOR during motor skill learning, we performed systemic and intrastriatal inhibitions of mTOR using the pharmacological inhibitor rapamycin, as well as a genetic knockdown of striatal mTOR using intrastriatal infusion of mTOR siRNA. These three independent approaches were all associated with a significant reduction in rotarod performances that were reminiscent of impaired consolidation processes. Notably, these treatments did not affect the capacity of mice to execute the pole test, suggesting that mTOR activity was mainly controlling motor learning rather than motor abilities. Moreover, all treatments decreased the levels of phosphorylated 4EBP1 and P70S6K, two molecular downstream targets of mTORC1. Our findings demonstrate that striatal mTOR, via the phosphorylation of 4EBP1 and P70S6K, play an important role in the cellular and molecular processes involved in motor skill learning.